PERILAKU SOSIAL ANAK USIA DINI BERAMBUT GIMBAL DI DAERAH DATARAN TINGGI DIENG KABUPATEN WONOSOBO - Mutmainah, Siti (Indonesian Journal of Early Childhood Education Studies, 2012)
Parentsâ treatment in educating children affects children behavior. In so doing, children will gain impression from their parentsâ. That later will help in formingÂ  theirÂ  social behavior.Â  This study is aimedÂ  toÂ  findÂ  out,describe,Â Â  and explain early childhood social behavior and the influence of parents treatment to ward earlyÂ  childhood with dreadlocks found in Dieng plateu, Wonosobo regency. The data are collected throughÂ  observation, questionnaire, interview,Â  and documentation, and then analyzed using data reduction, data presentation, conclusion-drawing, and verification. The study resulted that the social behavior of children at home is different with those at school. Beliefs about children with dreadlocks have become a culture triggering inhabitantsâ faith on the concept of parenting and treatment which should be given especially to children with dreadlocks. As those children are considered to be something entrusted and guarded by the holy spirit, every parent is obliged to give special treatment to those children. Special treatment given by the parents to children draws them to learn how to acquire something they desire. That way, children will show their angerÂ  whenever their wishes are not given byÂ  crying,Â  raging,Â  or doingÂ  other negative unwanted behaviors.